Morfologia, germinação e viabilidade de sementes de pereiro-vermelho (Simira gardneriana M.R. Barbosa & Peixoto) - Oliveira, Fabrícia Nascimento de (2014)
The pereiro-vermelho is a forest species belonging to the family Rubiaceae, considered endemic to the Caatinga and with little information in the literature, especially with regard to the morphology of seeds and seedlings, the initial stages of development and viability. Therefore, we carried out experiments in the laboratory of Seed Analysis and Morphology, anatomy, Federal Rural University of Semi-Arid, Mossoró-RN, in order to know the morphology of seeds and seedlings of pereiro-vermelho (Simira gardneriana MR Barbosa & Peixoto), as well as to assess the germination and viability of its seeds by the tetrazolium test. For the first experiment (Imbibition and morphological characterization of seeds and seedlings of pereiro-vermelho), four samples were used to evaluate 100 seeds length, width and thickness of the seeds, thousand seed weight, number seeds.kg-1, the water content, the water soaking curve, and descriptions of internal and external structures of the seeds and seedlings. The second experiment (seed germination pereiro-vermelho) was conducted in a completely randomized design, a 5 x 4 factorial arrangement, consisting of combinations of five substrates (sand between, on sand, paper roll, on paper and over vermiculite) and four temperatures (25 °C, 30 °C, 35 °C and 20-30 °C), with four replicates of 25 seeds each. In experiment (evaluation of seed viability by pereiro-vermelho tetrazolium), seeds of pereiro-vermelho were subjected to pre-wetting of paper roll for 144 hours at 30 °C and then placed in a solution of the tetrazolium 0.075%, 0.1%, 0.5% and 1.0% for 2, 4 and 6 hours at temperatures of 30 to 35 °C. The seeds were classified as viable or nonviable, according to pre-established parameters. The experimental design was completely randomized in a factorial 4 x 3 + 1, consisting of combinations of four concentrations of tetrazolium solutions, three periods of staining, and a control (germination test) for each tested temperature. Data were subjected to analysis of variance and the F test to compare the mean of viable seeds in the tetrazolium test with the results of the germination test was used were performed by Dunnett's test (p ≤ 0.05). The thousand seed weight was 69.04 g with average dimensions of 12.72 mm long, 8.25 mm wide and 1.12 mm thick. At 25 °C, the highest percentage of normal seedlings was found on paper roll substrate, however, did not differ statistically from the other substrates, except on paper. The seeds are albuminous pereiro-vermelho, the cotyledons are foliaceous, the germination is epigeal and seedlings are fanerocotylar. Temperatures of 25 °C and 30 associated with paper roll or sand substrates are suitable for the germination test. The tetrazolium test conducted with seeds soaked for 144 h at 30 °C between paper roll, followed by extraction of the embryo and color development for six hours in solution at a concentration of 0.075% in the temperature of 35 °C is adequate to assess the viability of seeds of pereiro-vermelho